RATIONAL INDICATORS OF GAS TRANSPORTATION BY GAS TRANSPORTATION SYSTEMS UNDER THE CONDITION OF THEIR INCOMPLETE LOAD - Hrudz, V. Ya.; Knysh, P. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The work is devoted to establishing the regularities of technological processes in gas transportation systems for optimizing operational control of operating modes under conditions of their incomplete loading. A mathematical model of non-stationary processes in a gas pipeline was created taking into account the influence of compressor stations on the basis of classical equations of gas flow energy and continuity using Dirac source functions. The implementation of the created mathematical model allowed obtaining in analytical form a dependence that reflects the law of oscillation in time of mass flow and pressure. The constructed dependences of the productivity trend of the gas transportation system at its beginning and at the end showed the influence of the placement of the compressor station in the gas transportation system, in particular its serial number on the route number, on the nature of the non-stationary process caused by its stop, in particular on the duration of non-stationarity.. Based on the research results, a principle of optimizing the operating modes of the gas transportation system under conditions of incomplete loading was proposed according to the criterion of minimum energy consumption for gas transportation at the maximum level of gas supply reliability.,